Accounting Information Systems of Mobile Telecommunication Companies in Bangladesh: An Evaluation - Neogy, Taposh Kumar (Asian Accounting and Auditing Advancement, 2016)
Accounting Information Systems are considered an important subsystem by all organizations for supporting their business operations. Accounting Information Systems are necessary for collecting, recording, maintaining, processing, and communicating relevant information to interested users so that they can use the information for effective decision making. At present Accounting Information Systems bear significance because they provide historical accounting information and help management evaluate past operations, control the present operations and decide the future operations of any business organization. The aim of the Accounting Information Systems of the selected mobile telecommunication companies is to produce information that helps make decisions at all levels of management and make logical choices among alternatives about a business entity. The importance of Accounting Information Systems is increasing day by day and it is used widely in every business organization. This study examines the existing Accounting Information Systems of the selected mobile telecommunication companies and found that the Accounting Information Systems of the selected mobile telecommunication companies are well organized. The selected companies give emphasis on the quality of accounting information produced by Accounting Information Systems through various statements. This paper recommends that the internal control system should be effective; the existing Accounting Information Systems should be upgraded through effective use of information technology. The system should be more users friendly and more security measures and control measures should be installed.